2020
DOI: 10.21203/rs.3.rs-79022/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Successful treatment of COVID-19 with remdesivir in the absence of humoral immunity

Abstract: The response to the coronavirus disease 2019 (COVID-19) pandemic has been hampered by lack of an effective severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antiviral therapy. Here we report the successful use of remdesivir in a patient with COVID-19 and the prototypic genetic antibody deficiency X-linked agammaglobulinaemia (XLA). Despite evidence of complement activation and a robust T cell response, the patient developed persistent SARS-CoV-2 pneumonitis, without progressing to multi-organ involv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…A major caveat to our findings is that our cohort is paediatric, for which both the clinical picture and outcome of SARS-CoV-2 infections are known to differ from adults. Notwithstanding, similar patterns of clinical and virological response to remdesivir have been described in adults (3,10,46,59) . Moreover, both clinical and viral sequence data from the use of repurposed drugs to treat other severe RNA viral infections has shown similarities in adults and children (12,50,55) .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A major caveat to our findings is that our cohort is paediatric, for which both the clinical picture and outcome of SARS-CoV-2 infections are known to differ from adults. Notwithstanding, similar patterns of clinical and virological response to remdesivir have been described in adults (3,10,46,59) . Moreover, both clinical and viral sequence data from the use of repurposed drugs to treat other severe RNA viral infections has shown similarities in adults and children (12,50,55) .…”
Section: Discussionsupporting
confidence: 61%
“…While several drugs with in vitro activity against SARS-CoV-2 have been identified, only remdesivir has shown any clinical promise (10) . However, reports of its efficacy are mixed (3,7–9,11) and only one other report of it having an effect on viral replication in vivo has been described (46) . We show evidence of clinical improvement in all three patients whilst on remdesivir.…”
Section: Discussionmentioning
confidence: 99%
“…Opinion articles, ecologic studies, and articles unrelated to COVID-19 hIEI clinical outcomes were excluded. Seven articles were included for nal analysis including three case reports [19][20][21]. three cohort studies [22][23][24], and one literature review of case reports [25].…”
Section: Selection and Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…The majority of patients ( 42) had common variable immunode ciency (CVID) [19,[22][23][24][25]. Thirteen patients had agammaglobulinemia (10 X-linked, three autosomal recessive) [21][22][23][24][25]. Five patients had speci c immunoglobulin de ciencies (IgG, IgA, or both) [20,[22][23][24]; four patients had otherwise unspeci ed hypogammaglobulinemia [22,23]; two patients each had hyper-IgM disease [22,24] and antibody de ciency with syndromic features [23]; and one patient had activated PI3K delta syndrome (APDS) [23].…”
Section: Humoral Inborn Errors Of Immunity -Effects On Covid-19 Diseamentioning
confidence: 99%
“…8,9,11,12 In COVID-19, a recent case report on a patient with complete absence of humoral immunity showed viral clearance following remdesivir administration. 37 A large J o u r n a l P r e -p r o o f retrospective cohort study of cancer patients with COVID-19 (N=2186) treated in the US also found a potential benefit for remdesivir with regard to mortality. 38 While the WHO does no longer recommend remdesivir for treatment of COVID-19 in the general population, this guideline panel still sees a potential benefit for immunocompromised cancer patients at risk of impaired viral clearance.…”
Section: Vaccinationmentioning
confidence: 99%